Promotional Efforts of Pharmaceutical Industries on Prescribing Pattern of Antibiotics among Medical Doctors in Nepal - Napit, Prabhat Ranjan (Journal of Business and Social Sciences Research, 2018)
Promotional efforts of pharmaceutical industries on prescribing pattern of antibiotics among doctors in Nepal” has been chosen as a topic for research to resolve certain queries among physicians’ behavior, particularly drug prescribing patterns as the influence of promotional approaches of pharmaceutical industry. The main objective of this research is to ascertain the various promotional activities of pharmaceutical industries of Nepal and find out its effects on prescribing pattern among physician in case of antibiotics along with rationality of prescription. For this study, data are collected both from primary as well as secondary sources. 225 sample size is taken from 4 districts (Kathmandu, Lalitpur, Bhaktapur and Kavre) to represent the country and convenient quota sampling is used to select the sample. The data are collected manually as the questionnaire is designed. From the data analysis, it is found that there is significant relationship between promotional efforts towards qualification of doctors and cost of antibiotics is considered as prioritized reason as well. And there is no significant relationship between patient compliance/ better quality among alternatives/ obligation (as a compensation of efforts)/ availability/ appearances as prioritized reason and promotional activities on qualification of doctors. Furthermore, there is significant relationship between influence of detailing/ gift/ monetary incentives/ trip and tours on prescribing pattern and rational prescription of antibiotics and no significant relationship between influence of samples and bonus on prescribing pattern and rational prescription of antibiotics. Journal of Business and Social Sciences Research, Vol. 1, No. 2, pp. 201-214